First observation of two hyperfine transitions in antiprotonic (3)He - Friedreich, S. (Elsevier Science, 2011)
We report on the first experimental results for microwave spectroscopy of the hyperfine structure of [Formula: see text]. Due to the helium nuclear spin, [Formula: see text] has a more complex hyperfine structure than [Formula: see text] , which has already been studied before. Thus a comparison between theoretical calculations and the experimental results will provide a more stringent test of the three-body quantum electrodynamics (QED) theory. Two out of four super-super-hyperfine (SSHF) transition lines of the [Formula: see text] state were observed. The measured frequencies of the individual transitions are 11.12559(14) GHz and 11.15839(18) GHz, less than 1 MHz higher than the current theoretical values, but still within their estimated errors. Although the experimental uncertainty for the difference of these frequencies is still very large as compared to that of theory, its measured value agrees with theoretical calculations. This difference is crucial to be determined because it is proportional to the magnetic moment of the antiproton.